Hubungan Frekuensi Antenatal Care Dengan Kejadian Komplikasi Persalinan di PMB Wilayah Jati Kota Probolinggo - Sinta Maharani Hanifah; Muthmainnah Zakiyyah; Iis Hanifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Complications during childbirth are the leading cause of maternal mortality in Indonesia. The incidence of labor complications can be prevented by frequent antenatal care (ANC) visits. Low frequency of antenatal care (ANC) may increase the risk of labor complications. The purpose of this study is to examine the correlation between the frequency of antenatal care and the incidence of labor complications in Independent Midwifery Practice Jati Area, Probolinggo City. This study used a cross-sectional research design with using secondary data from the Maternal and Child Health book and observation sheets. The number of samples in this study were 26 laboring mothers in the area in June 2024. The results of this study showed that the majority with low ANC frequency majority was 57.7%, incidence of labor complications was 61.5%. Fisher's test showed a significant correlation between the frequency of antenatal care and the incidence of labor complications with the result (p = 0.000). Suggestions for health workers, especially midwives, are expected to always provide motivation and knowledge about the importance of the frequency of antenatal care visits and need to improve the quality of antenatal care to prevent complications of labor.